2007
DOI: 10.1175/jas3978.1
|View full text |Cite
|
Sign up to set email alerts
|

Wave Energy Associated with the Variability of the Stratospheric Polar Vortex

Abstract: A study is performed on the energetics of planetary wave forcing associated with the variability of the northern winter polar vortex. The analysis relies on a three-dimensional normal mode expansion of the atmospheric general circulation that allows partitioning the total (i.e., kinetic ϩ available potential) atmospheric energy into the energy associated with Rossby and inertio-gravity modes with barotropic and baroclinic vertical structures. The analysis mainly departs from traditional ones in respect to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
(34 reference statements)
2
13
0
Order By: Relevance
“…This is as expected and consistent with previous studies, such as Liberato et al (2007), who found a strong lagged correlation between the stratospheric NAM index and wave-number one baroclinic waves. As mentioned earlier, we found that the geopotential height anomaly precursor of WVMs in Fig.…”
Section: Stationary Wave Forcingsupporting
confidence: 93%
See 1 more Smart Citation
“…This is as expected and consistent with previous studies, such as Liberato et al (2007), who found a strong lagged correlation between the stratospheric NAM index and wave-number one baroclinic waves. As mentioned earlier, we found that the geopotential height anomaly precursor of WVMs in Fig.…”
Section: Stationary Wave Forcingsupporting
confidence: 93%
“…It is known that stratospheric vortex anomalies are preceded by positive poleward anomalies in the zonal-mean heat fluxes in the lower stratosphere (Polvani and Waugh 2004) and increased baroclinic wave energy associated with planetary-scale waves (Liberato et al 2007;Castanheira et al 2009). However, the relationship between anomalous tropospheric planetary wave amplitudes and subsequent stratospheric variability is complex and dependent on the state of the stratosphere-troposphere system at the time of the generation of planetary wave anomalies (Reichler et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…1c) are also large near 1 and 25 February, but not all disturbances in the heat flux are exhibited in the stratospheric PW1 since the heat flux includes contributions from all waves. There is considerable evidence that amplified planetary scale disturbances in the winter stratosphere can be traced into the troposphere (Quiroz, 1979;Randel, 1987;Liberato et al, 2007).…”
Section: /2005 Wintermentioning
confidence: 99%
“…We analyzed the NH cool season (November to April) daily means of the horizontal wind components (u,v) and of the geopotential height, available on 17 standard pressure levels from 1000 to 10 hPa, on a 2.5 • ×2.5 • horizontal grid. The global horizontal wind (u,v) and geopotential(φ) fields were expanded in terms of the normal modes of the NCEP/NCAR reference atmosphere (see Liberato et al, 2007, and references therein for details), i.e.,…”
Section: Normal Mode Expansionmentioning
confidence: 99%
“…kinetic + available potential) energy per unit area associated with a given mode is proportional to the squared norm of the respective complex amplitude, w α msl (Liberato et al, 2007, and references therein)…”
Section: -D Normal Mode Schemementioning
confidence: 99%